Prevalence of myocardial injury in patients after acute ischaemic stroke according to standard criteria - Mihalovic, Michal; Mikulenka, Petr; Línková, Hana; Neuberg, Marek; Štětkářová, Ivana; Peisker, Tomáš; Lauer, David; Tousek, Petr (European heart journal supplements, 2023)
This study examined the prevalence of acute and chronic myocardial injury according to standard criteria in patients after acute ischaemic stroke (AIS) and its relation to stroke severity and short-term prognosis. Between August 2020 and August 2022, 217 consecutive patients with AIS were enrolled. Plasma levels of high-sensitive cardiac troponin I (hs-cTnI) were measured in blood samples obtained at the time of admission and 24 and 48 h later. The patients were divided into three groups according to the Fourth Universal Definition of Myocardial Infarction: no injury, chronic injury, and acute injury. Twelve-lead ECGs were obtained at the time of admission, 24 and 48 h later, and on the day of hospital discharge. A standard echocardiographic examination was performed within the first 7 days of hospitalization in patients with suspected abnormalities of left ventricular function and regional wall motion. Demographic characteristics, clinical data, functional outcomes, and all-cause mortality were compared between the three groups. The National Institutes of Health Stroke Scale (NIHSS) at the time of admission and the modified Rankin Scale (mRS) 90 days following hospital discharge were used to assess stroke severity and outcome. Elevated hs-cTnI levels were measured in 59 patients (27.2%): 34 patients (15.7%) had acute myocardial injury and 25 patients (11.5%) had chronic myocardial injury within the acute phase after ischaemic stroke. An unfavourable outcome, evaluated based on the mRS at 90 days, was associated with both acute and chronic myocardial injury. Myocardial injury was also strongly associated with all-cause death, with the strongest association in patients with acute myocardial injury, at 30 days and at 90 days. Kaplan-Meier survival curves showed that all-cause mortality was significantly higher in patients with acute and chronic myocardial injury than in patients without myocardial injury (P < 0.001). Stroke severity, evaluated with the NIHSS, was also associated with acute and chronic myocardial injury. A comparison of the ECG findings between patients with and without myocardial injury showed a higher occurrence in the former of T-wave inversion, ST segment depression, and QTc prolongation. In echocardiographic analysis, a new abnormality in regional wall motion of the left ventricle was identified in six patients. Chronic and acute myocardial injury with hs-cTnI elevation after AIS are associated with stroke severity, unfavourable functional outcome, and short-term mortality.
Keywords: Troponin; Cardiovascular disease; Myocardial injury; Stroke; Acute ischaemic stroke; Mortality